(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Worldwide, the incidence of diabetes mellitus is increasing due to the interaction of obesity, inflammation, and hyperglycemia. Immune activation and cytokine production lead to insulin resistance and other components of metabolic syndrome, establishing a link between diabetes and atherosclerosis. Endothelial dysfunction induced by hyperglycemia is associated with adventitious inflammation in experimental models of diabetic atherosclerosis and increased oxidative stress stimulating vascular vascular neovascularization. Recent studies have shown increased inflammation, neovascularization, and intraplatelet bleeding in human diabetic atherosclerosis. This is an inflammatory microangiopathic process associated with plaque rupture leading to coronary thrombosis on its own. The tissue factor, which is the most potent trigger of the coagulation cascade, increases in patients with diabetes mellitus and without glycemic control. Circulating tissue factor microparticles are also associated with platelet macrophage apoptosis, establishing a link between inflammation, platelet rupture, and blood thrombogenicity. High-density lipoproteins responsible for free cholesterol uptake are reduced in patients with insulin resistance and diabetes mellitus. Treatment with high-density lipoproteins leads to a significant reduction in platelet macrophages and an increase in smooth muscle cells. These effective effects may be responsible for the stabilization of coronary plaques in patients receiving the recombinant apolipoprotein AI Milano/phospholipid complex. Finally, peroxisomal proliferator-activated receptors (PPARs) are now considered regulators of nuclear transcription in atherosclerosis.